CS-03 LARGE CYSTIC INTRADURAL SCHWANNOMA IN CERVICAL REGION: A CASE REPORT. (16th December 2019) - Takeshima, Yuki; Takezaki, Tatsuya; Hamasaki, Tadashi; Tajiri, Seiji; Mukasa, Akitake
Abstract: Schwannomas are the most common intradural extramedullary spinal tumors. However, they are usually solid tumors, and totally cystic changes are rare. Herein, we report a case of a 46-year-old male presenting with numbness of right limbs, right hemiplegia, and posterior neck pain for one year. MRI revealed a well-defined cystic long-segment, from C1 to C6, intradural extramedullary mass. The lesion showed hypointense on T1WI, hyperintense on T2WI, hyperintense on DWI, and it was marginally enhanced on the contrast image with Gd-DTPA. C1 laminectomy and hemi-laminectomy from C2 to C6 was performed for tumor resection. The tumor was found to be totally cystic and tensed with a jelly-like content. It was completely resected with the attachment of the C3 dorsal root. Histopathological examination confirmed it to be a schwannoma. The mechanism of cyst formation in schwannoma is considered as results of ischemic necrosis associated with tumor growth, or cystosis due to degeneration of Antoni-type B region. The long-segment, totally cystic intradural cervical schwannoma is rare, bit it should be included in the differential diagnosis of a cystic mass in the spinal region. It can be difficult to distinguish cystic spinal schwannomas from other cystic lesions like arachnoid cyst, epidermoid cyst, and neurenteric cyst. Contrast enhanced MRI is useful by enhancing the margin of the tumor.